PEMBELAJARAN PEMAHAMAN MATEMATIKA PADA SISWA KELAS III SDN 259 GRIBA KOTA BANDUNG DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL - Peratiwi, Rima; Rahayu, Galih Dani Septiyan (COLLASE (Creative of Learning Students Elementary Education), 2021)
This study aims to examine learning mathematics understanding in grade III students using audio-visual media. The research method used is descriptive qualitative. Subjects in this study were students of class III SD Negeri 259 Griba Bandung City with a total of 27 students consisting of 11 male students and 16 female students. The instruments used were a teacher and student observation sheets, questions about simple fractions, and teacher and student questionnaires. The results showed that there was an increase in the quality of learning after using audiovisual media. This is indicated by the average value of class mathematics understanding of 80.15 which belongs to the good category, the highest score of students is 94 and the lowest score is 62. Students' learning completeness shows that 93.0% of students get scores above the minimum completeness criteria and 7. 0% still score below the minimum completeness criteria value.